Toward zero-excess lithium sulfur batteries: a systematic cell parameter study - Joshua H Cruddos; James B Robinson; Paul R Shearing; Alexander J E Rettie (JPhys Energy)
Zero-excess lithium (ZEL) or ‘anode-free’ batteries aim to minimize negative electrode material and address the challenges associated with handling thin lithium metal foils during fabrication. To date, most studies in the field of ZEL cells have primarily focused on lithium-ion chemistry, with considerably fewer systematic investigations into ZEL-sulfur (ZELiS) cell fabrication and optimization. Here we develop a ZELiS battery, comprising a Li _2 S-based composite positive electrode on carbon paper paired with a Ni foil current collector (CC) and evaluate the effects of various CC materials, electrolyte volume to Li _2 S mass ratio and C-rate. The developed cells reproducibly achieve an average Coulombic efficiency of 99% from cycles 2 to 200, and a final capacity of 272 mAh g ^−1 _Li2S at a C/10 rate. Furthermore, we employ x-ray computed tomography to elucidate the morphological changes and degradation processes occurring within the positive electrode composite, revealing the irreversible loss of Li _2 S/S _8 during cycling, which is exacerbated at high rates. These results should be useful in the development of commercially viable ZEL energy storage devices.